Dale Brown's dreamland : retribution - Brown, Dale, 1956-; DeFelice, James (New York : Harper, 2007)
The Dreamland team, headed by Lt. Colonel Tecumseh "Dog" Bastion, must avert a terrorist attack on America that will rival Pearl Harbor and September 11, 2001, combined--and they must do it short the two team members that have been lost at sea.
Adult.
Adult
Keywords: United States. -- Air Force -- Weapons systems -- Fiction; United States. -- Air Force -- Fiction; Air pilots, Military -- Fiction; Terrorism -- Fiction; Weapons systems -- Fiction; Air pilots -- Fiction; Military weapons -- Fiction; Terrorism -- Fiction